Analysis Of Service Quality Level Using Service Quality (Servqual) And SWOT Methods For Increasing Customer Satisfaction - Nasution, Alya Salsabila; Nadya, Yusri; Pramanda, Ryan (Jurnal Teknologi, 2024)
PT PLN Unit Layanan Pelanggan (ULP) Langsa is one of the implementing sub-units under the Customer Service Implementation Unit (UP3). The increase in the amount of electricity consumption is soaring high and fast, this has made the standard level of community satisfaction higher as a result of the increasing income of a modern society. A service is considered satisfactory if the service can meet the desires, expectations and needs of customers. The purpose of this study was to determine the gap between customer expectations and perceptions about the services of PT PLN ULP Langsa and the order of priority for service quality improvement that must be corrected first. One of the methods used to measure service quality is the Service Quality (Servqual) method. The results of calculating the servqual value obtained a gap value with all statement items, namely -2.23, this indicates that the services provided by PLN are currently still unable to provide optimal service to customers. Based on measurements of the 5 dimensions of Servqual, the results show that the five dimensions of service quality have values below 0 in order of priority for improvement, namely the Reliability dimension with a gap of -1.01, the Responsiveness dimension with a gap of -0.86, the Tangible dimension) with a gap of -0.62, the Assurance dimension with a gap of -0.56, and the Empathy dimension with a gap of -0.55. Based on the results of the SWOT analysis, the main improvement strategy proposed is the SO (Strength - Opportunity) strategy.